Creating New Fairytales: Statoil, Snøhvit, and Petroleum Exploration in the Arctic - Melissa Gjellstad (Scandinavian-Canadian Studies, 2014)
ABSTRACT: This paper investigates the valorization of the process of oil extraction in the High North as exemplified in corporate films and marketing materials produced by Statoil, a global energy company based in Norway. In focus is the subsea instillation of Snøhvit [Snow White] in the Barents Sea, an innovation on the frontier of the energy industry in the Arctic. In dialogue with Stephanie Le Menager’s “feeling ecological” theory and work with petromodernity, this article analyzes Statoil’s discourse in landscape, oil capitalism, and ecology to offer an interpretation of the evolution of the subsea extraction narratives in the Arctic waters as a new chapter in oljeeventyret [the oil fairytale] that began in Norway over forty years ago.